Risk analysis in textile industries using AHP-TOPSIS. (2021) - Bathrinath, S.; Bhalaji, R.K.A.; Saravanasankar, S.
Abstract: In terms of employment and economies textile industry is major contributor in several countries. In this sector both the large and small scale operations through contribute much to the economy also cause some risks to surrounding environment. Several processes are carried out to convert the fabric into yarn. These processes are more hazardous and it leads to accidents. The objective of this paper is to recognize and examine the possible risks that create accidents and critical alternative in the textile industry. This work has been performed in one of the leading textile industry in southern Tamilnadu, India. Henceforth, to recognize the most influential risks and prevention measures are being given for mitigating the risks and critical alternative for affecting the industrial performance using hybrid multi-criteria decision making method like Analytic Hierarchy Process (AHP) and Technique for order of preference by similarity to ideal solution (TOPSIS). Accidents are mainly happened because of poor lighting and ventilation, high noise and dust and also unwillingness of workers is the critical alternative in the textile industry.